Arctic Deltaic Lake Sediments As Recorders of Fluvial Organic Matter Deposition - Vonk, Jorien E.; Dickens, Angela F.; Giosan, Liviu; Hussain, Zainab A.; Kim, Bokyung; Zipper, Samuel C.; Holmes, Robert M.; Montlucon, Daniel B.; Galy, Valier; Eglinton, Timothy I. (Frontiers in Earth Science, 2016)
Arctic deltas are dynamic and vulnerable regions that play a key role in land-ocean interactions and the global carbon cycle. Delta lakes may provide valuable historical records of the quality and quantity of fluvial fluxes, parameters that are challenging to investigate in these remote regions. Here we study lakes from across the Mackenzie Delta, Arctic Canada, that receive fluvial sediments from the Mackenzie River when spring flood water levels rise above natural levees. We compare downcore lake sediments with suspended sediments collected during the spring flood, using bulk (% organic carbon, % total nitrogen, δ13C, Δ14C) and molecular organic geochemistry (lignin, leaf waxes). High-resolution age models (137Cs, 210Pb) of downcore lake sediment records (n = 11) along with lamina counting on high-resolution radiographs show sediment deposition frequencies ranging between annually to every 15 years. Down-core geochemical variability in a representative delta lake sediment core is consistent with historical variability in spring flood hydrology (variability in peak discharge, ice jamming, peak water levels). Comparison with earlier published Mackenzie River depth profiles shows that (i) lake sediments reflect the riverine surface suspended load, and (ii) hydrodynamic sorting patterns related to spring flood characteristics are reflected in the lake sediments. Bulk and molecular geochemistry of suspended particulate matter from the spring flood peak and lake sediments are relatively similar showing a mixture of modern higher-plant derived material, older terrestrial permafrost material, and old rock-derived material. This suggests that deltaic lake sedimentary records hold great promise as recorders of past (century-scale) riverine fluxes and may prove instrumental in shedding light on past behavior of arctic rivers, as well as how they respond to a changing climate.